PCR-Dipstick-Oriented Surveillance and Characterization of mcr-1- and Carbapenemase-Carrying Enterobacteriaceae in a Thai Hospital - Shanmugakani, Rathina Kumar; Akeda, Yukihiro; Sugawara, Yo; Laolerd, Warawut; Chaihongsa, Narong; Sirichot, Suntariya; Yamamoto, Norihisa; Hagiya, Hideharu; Morii, Daiichi; Fujiya, Yoshihiro; Nishi, Isao; Yoshida, Hisao; et al. (Frontiers in Microbiology, 2019)
Colistin is used as an alternative therapeutic for carbapenemase-producing Enterobacteriaceae (CPE) infections which are spreading at a very high rate due to the transfer of carbapenemase genes through mobile genetic elements. Due to the emergence of mcr-1, the plasmid-mediated colistin resistance gene, mcr-1-positive Enterobacteriaceae (MCRPEn) pose a high risk for the transfer of mcr-1-carrying plasmid to CPE, leading to a situation with no treatment alternatives for infections caused by Enterobacteriaceae possessing both mcr-1 and carbapenemase genes. Here, we report the application of PCR-dipstick-oriented surveillance strategy to control MCRPEn and CPE by conducting the PCR-dipstick technique for the detection of MCRPEn and CPE in a tertiary care hospital in Thailand and comparing its efficacy with conventional surveillance method. Our surveillance results showed a high MCRPEn (5.9%) and CPE (8.7%) carriage rate among the 219 rectal swab specimens examined. Three different CPE clones were determined by pulsed-field gel electrophoresis whereas only two MCRPEn isolates were found to be closely related as shown by single nucleotide polymorphism-based phylogenetic analysis. Whole genome sequencing and plasmid analysis showed that MCRPEn carried mcr-1 in two plasmids types – IncX4 and IncI2 with ~99% identity to the previously reported mcr-1-carrying plasmids. The identification of both MCRPEn and CPE in the same specimen indicates the plausibility of plasmid-mediated transfer of mcr-1 genes leading to the emergence of colistin- and carbapenem-resistant Enterobacteriaceae. The rapidity (< 2 h) and robust sensitivity (100%)/specificity (~99%) of PCR-dipstick show that this specimen-direct screening method could aid in implementing infection control measures at the earliest to control the dissemination of MCRPEn and CPE.